WACANA DAN TEORI REKABENTUK MENARA MASJID DI NUSANTARA (Discourse and Theory on Minaret’s Designs of Mosque in Malay Archipelago) - Ahmad, Azizul Azli; Ali@ Mat Zin, Aizan; Arbi, Ezrin (Journal of Al-Tamaddun, 2012)
Minaret is one of paramount importance elements in the development of Islamic Architecture nowadays. Three pivotal designs can be referred to by architects in designing minarets for a mosque. These designs of minaret usually linked to the influence of Byzantine; it is believed that they are the owner of minaret architecture. On the other hand, earlier than Byzantine period, Mesopotamian own the similar architecture; minaret. The issue here is who built it first; Byzantine or Mesopotamian? The paper analyzes the functions and symbol of minaret in Islamic architecture by scrutinizing the mosques in Malay Archipelago due to its significance appearance. The finding proves that minaret is not significant in Malay Archipelago due to its geographical factors.